Post-Transcriptional Regulation of Immune Responses and Inflammatory Diseases by RNA-Binding ZFP36 Family Proteins - Makita, Sohei; Takatori, Hiroaki; Nakajima, Hiroshi (Frontiers in Immunology, 2021)
Post-transcriptional regulation is involved in the regulation of many inflammatory genes. Zinc finger protein 36 (ZFP36) family proteins are RNA-binding proteins involved in messenger RNA (mRNA) metabolism pathways. The ZFP36 family is composed of ZFP36 (also known as tristetraprolin, TTP), ZFP36L1, ZFP36L2, and ZFP36L3 (only in rodents). The ZFP36 family proteins contain two tandemly repeated CCCH-type zinc-finger motifs, bind to adenine uridine-rich elements in the 3’-untranslated regions (3’ UTR) of specific mRNA, and lead to target mRNA decay. Although the ZFP36 family members are structurally similar, they are known to play distinct functions and regulate different target mRNAs, probably due to their cell-type-specific expression patterns. For instance, ZFP36 has been well-known to function as an anti-inflammatory modulator in murine models of systemic inflammatory diseases by down-regulating the production of various pro-inflammatory cytokines, including TNF-. Meanwhile, ZFP36L1 is required for the maintenance of the marginal-zone B cell compartment. Recently, we found that ZFP36L2 reduces the expression of Ikzf2 (encoding HELIOS) and suppresses regulatory T cell function. This review summarizes the current understanding of the post-transcriptional regulation of immunological responses and inflammatory diseases by RNA-binding ZFP36 family proteins.